2013
DOI: 10.1073/pnas.1304402110
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal structure determination of (Mg,Fe)SiO3postperovskite

Abstract: Knowledge of the structural properties of mantle phases is critical for understanding the enigmatic seismic features observed in the Earth's lower mantle down to the core-mantle boundary. However, our knowledge of lower mantle phase equilibria at high pressure (P) and temperature (T) conditions has been based on limited information provided by powder X-ray diffraction technique and theoretical calculations. Here, we report the in situ single-crystal structure determination of (Mg,Fe)SiO 3 postperovskite (ppv) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Apparently, the multigrain approach is an effective way to increase redundancy and completeness in data collection, thus significantly improving the HP singlecrystal data quality. HP multigrain XRD possesses great potential for the crystallographic studies of materials under HP, as demonstrated recently in studies of crystal structural determination of (Mg,Fe)SiO3 bridgmanite [194], post-bridgmanite [166], SiO2 [167], and -Ge [102].…”
Section: Hp Multiple Grain Xrdmentioning
confidence: 99%
See 3 more Smart Citations
“…Apparently, the multigrain approach is an effective way to increase redundancy and completeness in data collection, thus significantly improving the HP singlecrystal data quality. HP multigrain XRD possesses great potential for the crystallographic studies of materials under HP, as demonstrated recently in studies of crystal structural determination of (Mg,Fe)SiO3 bridgmanite [194], post-bridgmanite [166], SiO2 [167], and -Ge [102].…”
Section: Hp Multiple Grain Xrdmentioning
confidence: 99%
“…HP multigrain crystallography has been recently developed for single-crystal structure determination [151], which is particularly useful for studying the structural properties of phases that are not recoverable at ambient condition. For instance, structure refinement has been made for (Mg,Fe)SiO3 post-bridgmanite at pressures above one megabar [166]; electron density distribution of -Ge has been determined at 12 GPa [102,370]. With the precise structural determination enabled by the multigrain approach, it is anticipated that many previously determined HP structures will be revisited with the technique.…”
Section: Hp Crystallographymentioning
confidence: 99%
See 2 more Smart Citations
“…A further challenge in post-perovskite research is that singlecrystal samples cannot yet be synthesized by heating at high pressures. So, a combination of polycrystalline and single-crystal methods is being tried: individual grains in a polycrystalline sample are isolated and then subjected to single-crystal X-ray techniques 6,7 .…”
Section: Single Crystalsmentioning
confidence: 99%